Perencanaan Penanggulangan Kecelakaan Akibat Kerja di PD. Barokah Putri - Yusuf Mauluddin; Dedi Sa’dudin Taptajani; Intan Devita Sapitri (Jurnal Kalibrasi, 2022)
This study aims to obtain a production work safety and health plan in PD. Princess Baroque. Occupational accidents can cause production cost losses. Therefore, workplace accidents must be prevented, among other things, through risk analysis. One of the methods used is the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) method. This methodology consists of 3 phases: hazard identification, risk assessment, and determination of controls based on the data collected. Hazard identification is carried out through interviews and observations of employees and owners of tofu factories, and risk assessment is carried out by analyzing the likelihood and severity of risk for each potential hazard. After determining the risk index for each potential hazard, the next step is to determine risk management measures. Based on the research results, there are 36 potential hazards of tofu production based on high, low, medium and extreme risks, high-risk jobs including harvesting soybeans, grinding soybeans, cooking tofu, and sifting. Risk controls that can be implemented to reduce risk include designing automatic sorting machines, separating the milling and cooking processes, and using personal protective equipment (PPE) to ensure workers are safe and comfortable working, and installing them. Place warning signs in every corner of the hazardous production space to prevent unwanted things from happening.